Forensic Accounting And Fraud Examination - Lakshmi, Dr. T.Naga (International Journal of Scientific Research and Management (IJSRM), 2015)
Everyday across the world, thousands of businesses are victimized by fraud. Who commits these bad acts? Why? In addition, How? Until they grab hold of the fatality, it is a million dollar question that where the thousands of public money is disappearing. Every time Auditors and Chartered Accountants are catching hold of the frauds and victims – yet again after few days, months and years quite a few new frauds is committed. The impact of fraud can be devastating and the results can have deep consequences for the marketplace, organization, employees, clients and suppliers. As recent corporate incidents have shown, financial losses arising from fraudulent activity may lead to redundancies, factory closures, the loss of business opportunities or even business failure. The misappropriated funds might otherwise have been used to re-invest in the business, to build new facilities, create employment or develop better products and services. There is a need for forensic accounting in examining the frauds. The present paper focuses on what is the concept of Forensic Accounting and Fraud. What are different types of frauds? What are different types of accounts useful for forensic accounting? etc, and the Whistle Blowing Act relating to Forensic Accounting and Fraud Examination